KONSEP SALAMATUL FITRAH DALAM AL-QUR’AN (ANALISIS WACANA KRITIS DALAM SURAH YUSUF) - Rukman Abdul Rahman Said; Mubassyirah Bakri; Mubarak Bakri (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2023)
This article discusses the concept of the salamatul fitrah (nobility or purity of fitrah) in Surah Yusuf. The nobility of fitrah refers to the natural condition of humans who are born with a tendency to seek truth, goodness and beauty. This article reviews how humans can maintain the nobility of their fitrah through taqwa and obedience to Allah. In Surah Yusuf, taqwa is shown by the Prophet Yusuf when he refused the offer of adultery from Potiphar's wife even though it could give her worldly benefits. This concept teaches that humans must always maintain the nobility of their fitrah and always try to get closer to Allah. In Surah Yusuf, the nobility of fitrah can be seen from the character of Prophet Yusuf who always seeks truth and justice in the face of various obstacles. He also showed firmness of faith and patience in the face of severe trials. Apart from that, the concept of nobility of fitrah can also be seen in the attitude of Potiphar (the Egyptian dignitary) who bought Yusuf, as well as in the story of the Prophet Yusuf's brothers who were faced with jealousy and envy which led them to bad actions. In conclusion, the concept of the nobility of fitrah in Surah Yusuf teaches people to always improve themselves and face various tests of life with firmness of faith and patience. It is hoped that this article can provide a deeper understanding of the concept of the nobility of fitrah and how humans can improve it through piety and obedience to Allah.